Comparing Novel and Traditional Pharmacological Therapies in Acute Coronary Syndrome: Impacts on Short- and Long-term Health Outcomes - Skheta, Hana Abdelnaser; Jamour, Mukram Ayman; Khaffaf, Mafaz Al; Abdalla, Sohyla; Alhosani, Abeer; Alshehhi, Hamda; Alyassi, Aisha; Al-Beer, Amna Basel Kamil; Azzawi, Fatima Adel Jaafar Al; Alzarooni, Hind Tariq (Cardiology and Cardiovascular Medicine, 2025)
Acute coronary syndrome (ACS) is a group of diseases, including unstable angina and myocardial infarction provoked by the temporary occlusion of coronary arteries. ACS is still a major cause of morbidity and mortality across the globe. It continues to require rational pharmacological management to diminish the short-term outcomes and enhance long-term survival rates. Classical pharmacological interventions for ACS, aspirin, beta-blockers, and statins have been the stalwart of ACS therapy for numerous years. Though advanced treatments such as PCSK9 inhibitors and improved antiplatelet agents have joined the field, improving the patient's prognosis where potential risk is high remains a possibility. The goals of this SR were to evaluate current and novel pharmacological treatments concerning the prognosis of patients with ACS. To capture the effects of these therapies on short and long-term health outcomes, databases such as PubMed, Cochrane Library, and Embase were searched thoroughly to select the appropriate study. The collected data went through the extraction procedure, and their quality was evaluated by following the standardized research tools, thereby making the results more reliable. The analysis showed that, as the traditional treatments remain helpful in lessening the acute consequences, novel therapies are more effective in preventing recurrent CV events and increasing long-term survival, especially in high-risk patients. Nevertheless, these are novel treatment methods, and therefore expensive and are accompanied by some side effects that also pose a hindrance to their usage. The work underscores the importance of tailored therapeutic interventions based on the patient demographic, co-morbid conditions, and genetic makeup to enhance ACS care. Further studies should be addressed to raise the cost efficiency, longterm safety profile, and the issue of applying precision medicine in routine practice for ACS patients.